Strategic Disconnection in Islamic Mortgage Finance amid Socially Mediated Consumer Expectations - Dalimunthe, Fitriyani; Nasution, Muhammad Lathief Ilhamy; Harahap, Rahmat Daim (Celebes Scholar pg, 2025)
This paper carries out a critical analysis of the strategic performance and institutional articulation of the IB Griya mortgage financing product of PT. Bank Indoswara BNI Batam. Partly because the product is structurally sound, based on the Murabahah contract, and entirely compliant with the sharia related legal norms, continuing and inefficient performance in terms of meeting financing objectives illustrates more fundamental institutional morbidity. This study identifies five interlinked weaknesses through a qualitative approach of a case study method by combining in-depth interviews, an analysis of documents, and observations in the field, where five interconnected weaknesses are revealed including product-market inhomogeneity, inflexible and behaviorally inconsistent pricing policy, ineffective promotion communication, socially indifferent service provision, and an extreme lack of strategic planning and partnership building. Instead of blaming the macroeconomic fluctuation or consumer lack of knowledge, the results identify the issue on the epistemic structure and strategic culture within the institution. This paper maintains that Islamic mortgage finance will not perform based on mere juridical legitimation; however, it would be supported by the strategic reflexivity, relationship sense of trust development, emotional consistent service designing, and institutional behaviours run through the communities. So as evidenced by the case of IB Griya, unless it expands the narrative resonance, user-centric programming and multi-actor ecosystems of partnerships, there is a danger that sharia-compliant goods will become morally good, yet behaviorally peripheral.